Determinants hindering the intention of tourists to visit disaster-hit destinations. Issue 5 (4th April 2017) - Wang, Hsiu-Yuan
Abstract : The purpose of this study is to propose and examine a new research model that is able to capture both the cognitive and affective components influencing potential tourists' behavioural intentions to visit a disaster-hit destination, which have negatively affected their perceived destination image. A survey of 357 participants provides strong support for the model. The results indicate that participants' perceptions of destination image are a strong predictor of their travel intentions. Factors relating to cognitive appraisals (e.g. perceived equipment risk, perceived natural risk and perceived social risk) as well as affective evaluations (e.g. perceived fear of ghosts, perceived unpleasantness, etc.) were found to be critical components that significantly, and negatively, influence potential tourists' perceptions of a destination image. Theoretical and practical implications of the results are discussed herein.